Transcriptome analysis of Caenorhabditis elegans lacking heme peroxidase SKPO-1 reveals an altered response to Enterococcus faecalis. Issue 2 (30th December 2020) - Liu, Yi; Martinez-Martinez, Daniel; Essmann, Clara L; Cruz, Melissa R; Cabreiro, Filipe; Garsin, Danielle A
Abstract: The nematode Caenorhabditis elegans is commonly used as a model organism in studies of the host immune response. The worm encodes twelve peroxidase-cyclooxygenase superfamily members, making it an attractive model in which to study the functions of heme peroxidases. In previous work, loss of one of these peroxidases, SKPO-1 (ShkT-containing peroxidase), rendered C. elegans more sensitive to the human, Gram-positive pathogen Enterococcus faecalis. SKPO-1 was localized to the hypodermis of the animals where it also affected cuticle development as indicated by a morphological phenotype called "dumpy." In this work, a better understanding of how loss of skpo-1 impacts both sensitivity to pathogen as well as cuticle development was sought by subjecting a deletion mutant of skpo-1 to transcriptome analysis using RNA sequencing following exposure to control ( Escherichia coli ) and pathogenic ( E. faecalis ) feeding conditions. Loss of skpo-1 caused a general upregulation of genes encoding collagens and other proteins related to cuticle development. On E. faecalis, these animals also failed to upregulate guanylyl cyclases that are often involved in environmental sensing. Hoechst straining revealed increased permeability of the cuticle and atomic force microscopy exposed the misalignment of the cuticular annuli and furrows. These findings provide a basis for better understanding of the morphological as well as the pathogen sensitivity phenotypes associated with loss of SKPO-1 function.